2015
DOI: 10.17221/13/2014-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Mycological complex of poplars in Serbia

Abstract: Poplars are fast-growing broadleaved tree species inhabiting river banks and sites with accessible water supplies. Vegetative propagation makes them suitable for establishing highly productive plantations along big rivers and in flooded plains. The production of large quantities of biomass provides a good substrate for various organisms. The aim of this study was to identify fungal species occurring in the poplar plantations in Serbia and to determine their frequency and role in decomposition of tree parts. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The known host-Phytophthora associations of P. cactorum and P. plurivora and Populus spp. [4,[11][12][13] were confirmed by this study. In both the soil infestation and the underbark inoculation test, P. cactorum and P. plurivora demonstrated high aggressiveness to the roots and bark of poplar clones I-214 and Pánnonia.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The known host-Phytophthora associations of P. cactorum and P. plurivora and Populus spp. [4,[11][12][13] were confirmed by this study. In both the soil infestation and the underbark inoculation test, P. cactorum and P. plurivora demonstrated high aggressiveness to the roots and bark of poplar clones I-214 and Pánnonia.…”
Section: Discussionsupporting
confidence: 78%
“…Phytophthora cactorum had been isolated from bleeding cankers of Populus alba in the Czech Republic [11] and from the rhizosphere of young P. alba trees in Hungary [4], while P. × cambivora was recovered from poplar trees in Croatia [12]. A preliminary study demonstrated the presence of P. cactorum and P. plurivora in the rhizosphere of poplar trees in Serbia [13].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenicity of P. cac-torum has been assessed on young apple trees and apple fruits [33]. In Serbia P. cactorum has been reported on maple [34], in the soils of young hybrid poplar stands [35], on sycamore, walnut, common hawthorn, sessile oak, Hungarian oak, common alder, European wild pear and apple [36]. Having in mind these findings and the generally accepted view of P. cactorum as a generalist pathogen, we would expect that this plant pathogen is present on numerous other plant hosts in Macedonia.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together with a high demand for irrigation that provides natural means for Phytophthora spreading, poplar plantations are facing a serious threat. Indeed, recent reports have shown that Phytophthora species are already present in the rhizosphere under poplar trees, including aggressive species such as P. cactorum and P. plurivora ( Keča et al., 2016 ; Milenković et al., 2018 ). Following an artificial inoculation, both these pathogens induced a canker formation in the hybrid poplar clone T14 ( Ďurkovič et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%